'Unfortunate Jews' and urban ugliness: crafting a narrative of the 1391 assault on the jueria of Valencia. Issue 3 (27th May 2017) - Agresta, Abigail
ABSTRACT: On 9 July 1391, a mob assaulted the Jewish quarter of Valencia, killing and forcibly converting its inhabitants. This attack, one of many across Spain that summer, is much debated as a turning point in medieval Jewish history, but little attention has been paid to the role of the urban government. This article shows how the city council of Valencia shaped its narrative of the assault to further its goals for urban reform. In 1391, the Valencian council was in the midst of a reform initiative informed by the principles of Christian urban planning in Francesc Eiximenis' Regiment de la cosa pública . The jueria was seen as an impediment to reform. The council's retelling of the 1391 attack shifted responsibility onto the Jews and the jueria itself, considered a block to public order in the city. This laid the groundwork for the council's solution: the removal of the jueria from Valencia.